End-stage kidney diseases in areas of conflict: patients’ perspective and patient access to hemodialysis services in Northwest Syria - Ismail Alkhatib; Sami Alasfar; Gilbert Burnham; Nimetcan Mehmet Orhun (BMC Health Services Research)
Abstract Background There are an estimated 850 persons with End-Stage Kidney Disease (ESKD) receiving hemodialysis in the conflict-affected Northwest Syria. This study examines patients’ perspectives, and experiences with hemodialysis and their knowledge about their disease and treatment. Methods This study used telephone interviews with 101 randomly selected ESKD patients from 12 of the 14 hemodialysis units in Northwest Syria during early 2023 in a cross-sectional study. Results The mean age of respondents was 50.3 ± 16.7 years (range 7 to 81), with 55.4% males. The sample included 53 local residents and 48 Internally Displaced Persons (IDPs) from elsewhere in Syria. A quarter (28.7%) of patients reported being unable to access one or more hemodialysis sessions in the previous year. In the past year, 61 of 101 dialysis patients had changed household location because of reported insecurity. Frequent household relocations disrupted dialysis continuity resulting in the use of multiple dialysis sites. Because of the decentralized distribution of facilities, half of patients could reach their dialysis facility in 30 min or less, and at minimal costs. Two-thirds (67.3%) reported the presence of comorbidities, with hypertension and diabetes being the most common. Of the 35 patients with diabetes, 15 required insulin. Only about half (52.5%) had seen a nephrologist or physician in the past six months. The health literacy level concerning ESKD, and hemodialysis was low for many patients. Conclusion While considerable resilience is seen among hemodialysis patients in conflict areas of Northwest Syria, there are deficits in care and health literacy concerning ESKD and hemodialysis which should be addressed. There are a number of low resource actions which could be undertaken for this population to improve their health and understanding of their disease which are currently being considered.